Interactions between season of birth, chronological age and genetic polymorphisms in determining later-life chronotype. (June 2020) - Didikoglu, Altug; Maharani, Asri; Canal, Maria Mercè; Pendleton, Neil; Payton, Antony
Highlights: Genetic variants that are related to epigenetic regulations and DNA repair may be associated with age-dependent variations of chronotype. Postnatal seasons may program biological rhythms via epigenetic alterations and neural development. Some polymorphisms contribute towards inter-individual variation in season of birth effect. Previously reported genetic variants that were associated with chronotype could not fully explain the longitudinal change of chronotype. Abstract: Human chronotype, the temporal pattern of daily behaviors, is influenced by postnatal seasonal programming and ageing. The aim of this study was to investigate genetic variants that are associated with season of birth programming and longitudinal chronotype change. Longitudinal sleep timing and genotype data from 1449 participants were collected for up to 27 years. Gene-environment interaction analysis was performed for 445 candidate single nucleotide polymorphisms that have previously been associated with chronotype. Associations were tested using linear mixed model. We identified 67 suggestively significant genomic loci that have genotype-ageing interaction and 25 genomic loci that may have genotype-season of birth interaction in determining chronotype. We attempted to replicate the results using longitudinal data of the UK Biobank from approximately 30, 000 participants. Biological functions of these genes suggest that epigenetic regulation of gene expression and neural development may have roles in these processes. The strongest associated gene for sleep trajectories was ALKBH5, which has functions of DNA repair and epigenetic regulation. A potential candidate gene for postnatal seasonal programming was SIRT1, which has previously been implicated in postnatal programming, ageing and longevity. Genetic diversity may explain the heterogeneity in ageing-related change of sleep timing and postnatal environmental programming of later-life chronotype.